قراءة في قصيدة أدونيس (تاريخ يتمزق في جسد امرأة) - عيسى, حكمت; مخلوف, نور (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
لقد خلق الله الإنسان على صورته, والإنسان هنا يُقصد به الرّجل والمرأة على حدّ سواء, إلاّ أنّ المرأة في مجتمعاتنا ما زالت تعاني, وتبحث عن مخرج لتحقيق ذاتها, وتناضل من أجل إثبات حضورها الإنسانيّ الكامل. ولما كانت هذه المجتمعات, مجتمعات دينيّة تحكمها الشرائع التي حدّدها الأسلاف, وفقاً لرؤاهم وفهمهم للنّص الديني, وتطلعاتهم السلطويّة, تحولت هذه المجتمعات إلى مجتمعات ذكوريّة همّشت المرأة, وتعاملت معها ككيان ناقص, وتابع للرجل. ورأى أدونيس أنّ هذه المجتمعات لن تتحرر من أغلال التخلّف , إلا بتحرير المرأة. لعل " تاريخ يتمزق في جسد امرأة " قصيدة تعبر عن رأي أدونيس بالدين والمجتمع والمرأة والفكر التقليدي, والتّراث الثقافي, وموقفه من السلطة الذكوريّة, والجنس. God created man in his own image, man here is intended both for men and women. but the women in our societies still suffer and look for a way to prove its full humanit arian presence. As these communities, religious communities are governed by the iaws set by the progenitors according to their vision and understanding of the religious text and authoritarian aspirations. These communities turned into a masculine communities which marginalized women and dealt with as an entity minus continued to the man. Adounis saw that these communities will not be liberated from the shackles of back wardness however, women`s emancipation. The history of ruptures in a woman`s body), perhaps is a poem reflects the opinion of Adounis religion and society, women and traditional thinking, cultural heritage, and his position of masculine authority and sex.